2018
DOI: 10.1186/s13104-018-3382-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and phenotypic characterization of Enterococcus species isolated from clinical samples of pediatric patients in Jimma University Specialized Hospital, south west Ethiopia

Abstract: ObjectiveThis study was done to determine the prevalence and phenotypic characterization of Enterococcus species isolated from clinical samples of pediatric patients in Jimma University Specialized Hospital, Southwest Ethiopia.ResultsThe overall prevalence of Enterococci species was 5.5% (22/403). Five (22.7%) of Enterococci species were vancomycin resistant. Haemolysin, gelatinase and biofilm production was seen among 45.5, 68.2 and 77.3% of isolates respectively. The overall rate of antibiotic resistance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 30 publications
9
21
9
Order By: Relevance
“…Moreover, the present study also showed that 49.6% of Enterococci isolates were multidrug resistant. This result is lower than the ndings in Iraq (85.7%) (17) and Ethiopia 80.8% (41). In contrary, the result is higher than the nding in Ethiopia 29.5% (16).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Moreover, the present study also showed that 49.6% of Enterococci isolates were multidrug resistant. This result is lower than the ndings in Iraq (85.7%) (17) and Ethiopia 80.8% (41). In contrary, the result is higher than the nding in Ethiopia 29.5% (16).…”
Section: Discussioncontrasting
confidence: 66%
“…The gradual increase in the prevalence of VRE might have contributed to this higher prevalence as supported by other studies (32,38). (41) erythromycin; This lower resistance pattern might be due to variation in study participants in which most of the participants in the previous studies were hospitalized patients who were taking different antibiotics that might be contributed for emergence of high rate of drug resistant microorganisms including Enterococci.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the studies were reported from Amhara region (n = 8) [30][31][32][33][34][35][36][37] and Addis Ababa (n = 7) [38][39][40][41][42][43][44]. The remaining studies were from Oromia (n = 4) [45][46][47][48] and Southern nations (n = 1) [23]. Studies were not available from administrative regions of Tigray, Afar, Dire Dawa, Harari, Somali, Gambela and Benishangul-Gumuz.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Enterococci have long been considered symbiotic organisms of humans that have the potential to accidentally invade the host [1]. Recently, Enterococcus species have emerged as important pathogens causing hospital-acquired and community-acquired abdominal infections [2]. The common infection sites are the urinary tract, surgical sites, respiratory tract, gastrointestinal tract, skin and soft tissue.…”
Section: Introductionmentioning
confidence: 99%